On the presence of Anastatus tenuipes (Hymenoptera, Eupelmidae) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Anastatus tenuipes Bolivar y Pieltain, 1925 (Hymenoptera,Eupelmidae), parasitoid of oothecae of Supella longipalpa (F.) (Blattaria,Blattellidae) is newly reported for Italy and Europe. Main data on diagnostic characters,biology and distribution of the species are given.
Keywords: Hymenoptera Eupelmidae; Blattaria Blattellidae; natural enemy; Supella longipalpa; new record